(3efgL GdSGdc Edi CdajI GHf eGdcs - (3GdCTehfj, CHh GdMSf, fhQ GdOjf, Ydj Hf eMeO, J fMh (B900 (3g`s
(3ChdgG (B:s
(3MeOG ddg Ydi eG efM ef CSHGH GdHjGf haJM ef CHhGH GdJHjGf agPG TQM dWja HOjY Ydi CdajI GHf eGdc hbO dbHJg HefgL GdSGdc Edi CdajI GHf eGdcs
(3BNQgG (B:s
(3abGd QMeg Gddg hLeYfj hEjGg aj OGQ GdSdGe (B: (3aCMeO Gddg eUdjG Ydi eMeO NjQ fHj CQSdG hBdg GdZQ GdcQGe GdHQQI hUMHg GdefJNHjf GdNjQIs
(3fSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 10s
(3eYLe GdeDdajf(B: 2 / 407s
(3cTa GdXfhf(B: 1 / 153s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs